2017
DOI: 10.1063/1.4975304
|View full text |Cite
|
Sign up to set email alerts
|

Charge and topography patterned lithium niobate provides physical cues to fluidically isolated cortical axons

Abstract: In vitro devices that combine chemotactic and physical cues are needed for understanding how cells integrate different stimuli. We explored the suitability of lithium niobate (LiNbO3), a transparent ferroelectric material that can be patterned with electrical charge domains and micro/nanotopography, as a neural substrate. On flat LiNbO3 z-surfaces with periodically alternating charge domains, cortical axons are partially aligned with domain boundaries. On submicron-deep etched trenches, neurites are aligned wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In the future, we plan to utilize pyroelectrification techniques for micro-object patterning as well as LiNbO 3 and lithium niobate as a neuron substrate to quantify and measure biomaterial-induced changes in cell behavior. [38][39][40] These platform technologies can be combined with SLIM for probing neuronal behaviors, such as neurite outgrowth and branching, at the subcellular level in topographically and chemically controlled environments. Using SLIM to quantitatively measure neurite outgrowth dynamics in a broader context has the potential to help elucidate the complex environmental and intrinsic signals that regulate and modulate neuritic outgrowth, pruning, and arborization-the substrate for neuronal function.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the future, we plan to utilize pyroelectrification techniques for micro-object patterning as well as LiNbO 3 and lithium niobate as a neuron substrate to quantify and measure biomaterial-induced changes in cell behavior. [38][39][40] These platform technologies can be combined with SLIM for probing neuronal behaviors, such as neurite outgrowth and branching, at the subcellular level in topographically and chemically controlled environments. Using SLIM to quantitatively measure neurite outgrowth dynamics in a broader context has the potential to help elucidate the complex environmental and intrinsic signals that regulate and modulate neuritic outgrowth, pruning, and arborization-the substrate for neuronal function.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…83,[85][86][87][88][89] Therefore, intracellular [Ca 2+ ] changes seem to us a very important signaling element, that may have a crucial role in the observed cell responses to excited ferroelectrics. [28][29][30][31]35,59 As Ca 2+ has also been involved in the regulation of other critical responses such as cell proliferation, 85 contractibility, 86 or differentiation/dedifferentiation 88 to name a few, this signaling ion could have a relevant role in other reported biological responses to ferroelectrics: osteoblastic differentiation 60,64 or enhanced proliferation. [61][62][63][64][65][66] It deserves mentioning that, although Ca 2+ signaling features the largest number of studies in the field of electric biomodulation, there are some works shedding light upon other relevant voltage-gated channels, like Na + channels 86 or K + channels, 85 to explain cellular responses to electric fields.…”
Section: B Electrokinesismentioning
confidence: 99%
“…Recent work regarding charged substrates has been targeted toward the study of lithium niobate (LiNbO 3 ), a ferroelectric material that has a spontaneous polarization, P S = 0.71 C m −2 along its polar axis. Prior studies have shown that nonfunctionalized LiNbO 3 surfaces are biocompatible with osteoblasts, mesenchymal stem cells, and neurotypic cells . The polarity of LiNbO 3 has been shown to drastically affect osteoblast cell behavior .…”
Section: Spontaneous and Piezoelectric Polarization Effectsmentioning
confidence: 99%
“…In a representative study by Marchesano et al, fibroblast cells (NIH 3T3) showed a quantifiable dependence on polarity—the cytoskeletal spreading was visualized during microscopy studies and showed a significant enhancement on the negative face of the inorganic LiNbO 3. Etched and patterned LiNbO 3 has also been utilized to align neurites in vitro based on surface charge and topography . Recently there have been several novel techniques developed to investigate the polarization of LiNbO 3 on cell behavior using holographic total‐internal‐reflection microscopy (HoloTIRM) and spatial light‐interference microscopy .…”
Section: Spontaneous and Piezoelectric Polarization Effectsmentioning
confidence: 99%